Link of apoptosis level in the primary tumor at early stages of non-small cell lung cancer with efficacy of adjuvant polychemotherapy - Kolesnik O.P.; Shevchenko A.I.; Tumansky V.O.; Shyshkin M.A.; Yevseyev A.V. (Medičnì Perspektivi)
One of the important questions in modern oncology is treatment of patients with early stages of non-small cell lung cancer (NSCLC). Adjuvant polychemotherapy (APCT) can help to improve prognosis after operation. In modern literature there is no unified opinion as for patients in need of adjuvant chemotherapy. However, now investigators indicate to necessity to use molecular markers for individualization of APCT. The aim of our study was to assess correlation between apoptos level in primary tumor in patients with early stages of NSCLC with effectiveness of APCT. Study was conducted by the chair of oncology of Zaporozhye state medical university since June 2008 to Dec 2012. 254 patients with I-II stages of non-small cell lung cancer were included in the study. Expres¬sion of p53 was evaluated as percent of positively stained nucleus tumor cells in general population. More than 25% of positively stained nucleus tumor cells meant high p53 expression. Results: We performed assessment of apoptosis level with the help of p53 expression in 220 patients. No prognostic significance of p53 level expression in patients with early stages of non-small cell lung cancer (р=0,65) was revealed. There was significant correlation between age (р=0,039), sex (р=0,009) and apoptosis level in primary tumor in patients with early stages of NSCLC. Worse survival was noted in group of patients with low p53 expressions after adjuvant chemotherapy (р=0,009). But in patients with high level of p53 expression adjuvant chemotherapy significantly increased survival (p<0,001). So, adjuvant chemotherapy in patients with I-II stages of NSCLC is necessary to be carried out in cases of high p53 expression level.